KERUPUK NASI GURIH DAN SEHAT UNTUK BERBAGAI KALANGAN - Nur Alya Ramadani; Kumala Sari, Riska; Andri; Dion Praja; Tilka; Sapar (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2024)
Utilizing rice crackers to become a healthy food product that is highly nutritious and has marketable value, the aim of the student-entrepreneurship creativity program (PKM-K) is to raise students' motivation to become entrepreneurs in processing rice crackers into healthy food products that are nutritious and have sales value. Consuming yogurt is very useful for health, and strengthening bones and teeth, the methods for implementing this program are input, process (production), output, and evaluation. The results of this program are input, conducting market surveys to determine market conditions. Next is a feasibility study of the business that will be run. The final stage is selecting materials and providing a place as well as facilities and infrastructure to support the production process. Process (production), is the process of making rice crackers starting from preparing the ingredients and tools until the rice crackers are ready to be marketed. Output, namely the results of rice crackers that are ready to be consumed and marketed to consumers. The final one is evaluation, namely this stage is carried out when the production of rice crackers has been completed. At this stage, we will review what shortcomings make consumers dissatisfied with consuming our products. The PKM-K program concludes that the use of rice crackers in healthy food products that are highly nutritious and have marketable value can provide students with the skills to remain innovative and creative in managing healthy drinks. Keywords: Healthy, Rice Crackers, Nutritious.